Critical Literacy and the Un/Doing of Academic Discourse - Taylor, Catherine (Ethnologies)

(untitled) (Association Canadienne d'Ethnologie et de Folklore, 2004)
AbstractThis article describes a “critical literacy” approach to teaching an introductory course in academic writing to a group of students socially marginalized by poverty and prejudice. In this approach, the author asks students to identify research areas of personal interest to themselves by drawing on their own lives to generate meaningful topics, to engage in critical dialogue about their work, and to write in a scholarly style without becoming alienated from their work. She also welcomes students’ critical observations on their own experience of dominant culture and invites them to scrutinize the academic world they are entering as an institution that participates fully in systems of privilege and power. In her experience, much of the work done by students engaged in a such an approach demonstrates a higher degree of the critical insight and serious-minded knowledge-building valued in academia than is normally seen in introductory writing courses. She articulates a rationale for using this empowerment-based method of teaching academic writing in the face of calls for a return to traditional methods, and provide an analysis centred in Critical Literacy theory to account for its successes and challenges.